RESEARCH ON THE USE OF ECO-DRIVING IN CITY TRAFFIC (Perner's Contacts, 2021)
As it is commonly known, during the operation of vehicles, their operational parameters change, related to the influence of working factors, the current road situation or wear processes of vehicle components. Currently, for many years there has been a discussion on improving the environmental properties of motor vehicles, taking into account technical, legal and operational factors. The article presents selected research results of a vehicle using the eco-driving technique in city traffic on the so-called routine route in a selected area of the city of Lublin in south-eastern Poland. The tests were carried out on a passenger car with a spark ignition engine powered by gasoline. The obtained test results focus on the influence of selected driving parameters, such as: average speed, driving time, mileage, road characteristics, number of stops, number of brakes. The conducted research indicates the possibility of using eco-driving in city traffic and gives positive results.